2016
DOI: 10.4258/hir.2016.22.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Alarms in Intensive Care Units: Perceived Obstacles of Alarm Management and Alarm Fatigue in Nurses

Abstract: ObjectivesThe purpose of this descriptive study was to investigate the current situation of clinical alarms in intensive care unit (ICU), nurses' recognition of and fatigue in relation to clinical alarms, and obstacles in alarm management.MethodsSubjects were ICU nurses and devices from 48 critically ill patient cases. Data were collected through direct observation of alarm occurrence and questionnaires that were completed by the ICU nurses. The observation time unit was one hour block. One bed out of 56 ICU b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
113
3
23

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(150 citation statements)
references
References 19 publications
11
113
3
23
Order By: Relevance
“…Many studies have demonstrated that 72%–99% of clinical alarms may be inaccurate 1 3 4 6. Also, overuse of clinical and bedside monitoring devices has led to a tremendous increase in false and unreliable alarms, significantly contributing to AF 7. In 2014, The Joint Commission and the Food and Drug Administration recognised AF as a ‘national healthcare problem’ that is among the top 10 technology hazards in hospitals 3 8 9.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have demonstrated that 72%–99% of clinical alarms may be inaccurate 1 3 4 6. Also, overuse of clinical and bedside monitoring devices has led to a tremendous increase in false and unreliable alarms, significantly contributing to AF 7. In 2014, The Joint Commission and the Food and Drug Administration recognised AF as a ‘national healthcare problem’ that is among the top 10 technology hazards in hospitals 3 8 9.…”
Section: Introductionmentioning
confidence: 99%
“…However, sound levels in hospitals and patient rooms can surpass these recommendations, as levels have been measured between 43 dB (eg, the sound of birdcalls) at night and as high as 85 dB (eg, a food blender) throughout the day 1,3–5. It is important to note that these hospital sound recommendations date from 1999,2 at which time there were approximately 6 types of alarms in a critically ill patient's room 6. By 2011, there could be as many as 40 types of alarms in a patient's room, despite research to suggest that nurses have difficulty differentiating between more than 6 distinct alarm sounds 6…”
mentioning
confidence: 99%
“…Alarm fatigue, cognitive overload and desensitization, and its consequences, fatal and near-fatal events as well as staff burnout and the "second-victim effect", are almost invariably described qualitatively. The work by Cho et al [13] targeting a scoring system for AF using on a questionnaire based on the HTF survey [14] was a first step to come to a quantification of alarm fatigue. There is, to the best of our knowledge, no published attempt to make the various facets of AF routinely measurable and comparable in a comprehensive manner, i.e.…”
Section: A the Measurability Gapmentioning
confidence: 99%